Cytotoxicity, Total Phenolic Content and Antioxidant Activity of Bergenia purpurascens Rhizome - Bajracharya, Gan B; Maharjan, Rokesh (Nepal Journal of Science and Technology, 2013)
This study was aimed to evaluate the cytotoxicity of methanolic extract (ME) and aqueous extract (AE) of the rhizomes of Bergenia purpurascens through the Brine-shrimp bioassay, which revealed that ME possessed cytotoxicity with LC50 = 181.97 ìg/ml value. The plant extracts were also evaluated in vitro for antioxidant activity using different redox [Folin-Ciocalteu (FC) and Ferric Reducing Antioxidant Power (FRAP)] and radical scavenging [(2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2’-azinobis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS)] assays. Both ME and AE possessed antioxidant activity and ME displayed comparatively a greater potential. The total phenolic contents in ME and AE was 1.27 and 0.06 g gallic acid equivalent (GAE)/100 g dry mass (DM), respectively. The FRAP values determined for ME and AE were 15.82 and 2.58 ìmol Fe(II)/100 g DM, respectively. The DPPH radical scavenging effect (IC50) was for ME 19.86 ìg/ml and 295.91 ìg/ml for AE. At 100 ìg/ml concentration, up to 94% inhibition of ABTS+ was observed in 6 min incubation. Nepal Journal of Science and Technology Vol. 14, No. 1 (2013) 87-94 DOI: http://dx.doi.org/10.3126/njst.v14i1.8927